1998
DOI: 10.1007/s002200050306
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Quantization and Two Dimensional QCD

Abstract: In this article, we will discuss geometric quantization of 2d QCD with fermionic and bosonic matter fields. We identify the respective large-N c phase spaces as the infinite dimensional Grassmannian and the infinite dimensional Disc. The Hamiltonians are quadratic functions, and the resulting equations of motion for these classical systems are nonlinear. In [33], it was shown that the linearization of the equations of motion for the Grassmannian gave the 't Hooft equation. We will see that the linearization in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 33 publications
1
44
0
Order By: Relevance
“…Using exactly the same methods as in [7,18], we can show that it is closed and nondegenerate. In fact the above form is also a homogeneous two-form invariant under the group action, as can be verified in a simple manner.…”
Section: The Algebra Of Color Invariant Operatorsmentioning
confidence: 95%
See 3 more Smart Citations
“…Using exactly the same methods as in [7,18], we can show that it is closed and nondegenerate. In fact the above form is also a homogeneous two-form invariant under the group action, as can be verified in a simple manner.…”
Section: The Algebra Of Color Invariant Operatorsmentioning
confidence: 95%
“…The other possibility is to write the symplectic form in the action and use single valuedness of the path integral as is done in [7]. (We note in passing that there is a factor of 2 missing in the reference [18], due to an error in the conventions, but we scale the Hamiltonian with the same parameter so the large-N c results are the same. The geometric quantization parameter instead should have been 1/N c ).…”
Section: The Algebra Of Color Invariant Operatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Scalar QCD was worked out using the same methods in Ref. 9, where it was shown that the phase space of the theory is an infinite dimensional disk. Originally scalar two-dimensional QCD was worked out by Shei and Tsao in Ref.…”
Section: Introductionmentioning
confidence: 99%